Performance and Usability Evaluation of Brainwave Authentication Techniques with Consumer Devices - Arias-Cabarcos, Patricia; Fallahi, Matin; Habrich, Thilo; Schulze, Karen; Becker, Christian; Strufe, Thorsten (ACM Transactions on Privacy and Security)
Brainwaves have demonstrated to be unique enough across individuals to be useful as biometrics. They also provide promising advantages over traditional means of authentication, such as resistance to external observability, revocability, and intrinsic liveness detection. However, most of the research so far has been conducted with expensive, bulky, medical-grade helmets, which offer limited applicability for everyday usage. With the aim to bring brainwave authentication and its benefits closer to real world deployment, we investigate brain biometrics with consumer devices. We conduct a comprehensive measurement experiment and user study that compare five authentication tasks on a user sample up to 10 times larger than those from previous studies, introducing three novel techniques based on cognitive semantic processing. Furthermore, we apply our analysis on high-quality open brainwave data obtained with a medical-grade headset, to assess the differences. We investigate both the performance, security, and usability of the different options and use this evidence to elicit design and research recommendations. Our results show that it is possible to achieve Equal Error Rates as low as 7.2% (a reduction between 68–72% with respect to existing approaches) based on brain responses to images with current inexpensive technology. We show that the common practice of testing authentication systems only with known attacker data is unrealistic and may lead to overly optimistic evaluations. With regard to adoption, users call for simpler devices, faster authentication, and better privacy.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Run-to-Failure Relay Dataset for Predictive Maintenance Research With Machine Learning - Winkel, Fabian; Deuse-Kleinsteuber, Johannes; Böcker, Joachim (IEEE Transactions on Reliability)
Keywords: Electrical and Electronic Engineering; Safety; Risk; Reliability and Quality

A model of cycles and bubbles under heterogeneous beliefs in financial markets - Burs, Carina (Cogent Economics & Finance)
I study the effect of heterogeneous beliefs about asset prices on the long-term behavior of financial markets. Starting from the ideas of Abreu and Brunnermeier (Citation2003), a two-dimensional system of differential equations is developed. The first dynamic variable is the asset price growth rate. The second dynamic variable is the number of investors who believe that asset prices are abnormally high. In a phase plane analysis, I find both stable and unstable equilibria, depending on the spread of information and the response to other agents’ beliefs. If individuals try to increase their returns while perceiving more overpricing, these equilibria can be spirals or even approach limit cycles. Although I intend to study general price patterns, abnormally high asset prices can be caused by financial bubbles. In this model, bubbles can emerge and deflate both in cycles or directly, or they can grow until they burst. Further, I analyze market behavior after a central bank increases the interest rate. This can lead to new stable equilibria, but the emergence and bursting of bubbles cannot be prevented.
Keywords: asset pricing; subjective information; stability conditions; monetary policy; risk aversion

Business Reputation Systems based on Blockchain Technology—A Risky Advance - Hemmrich, Simon (Proceedings of 31st European Conference on Information Systems (ECIS 2023))
Reputation is indispensable for online business since it supports customers in their buying decisions and allows sellers to justify premium prices. While IS research has investigated reputation systems mainly as review systems on online platforms for business-to-consumer (B2C) transactions, no proper solutions have been developed for business-to-business (B2B) transactions yet. We use blockchain technology to propose a new class of reputation systems that apply ratings as voluntary bonus payments: Before a transaction is performed, customers commit to pay a bonus that is granted if a service provider has performed a service properly. As opposed to rival reputation systems that build on cumulated ratings or reviews, our system enables monetized reputation mechanisms that are inextricably linked with online transactions. We expect this system class to provide more trustworthy ratings, which might reduce agency costs and serve quality providers to establish a reputation towards new customers, building on second-order trust.
Keywords: Trust; Risk; Reputation System; Blockchain Technology; Business Reputation System.

Coalition formation versus free riding in rent-seeking contests - Block, Lukas (Quick And Easy Journal Title)
We study lobby group formation in a two-stage model where the players rst form lobby groups that then engage in a rent-seeking contest to inuence the legislator. However, the outcome of the contest aects all players according to the ideological distance between the implemented policy and the players' preferences. The players can either lobby by themselves, form a coalition of lobbyists or free ride. We nd that free coalition formation is reasonable if either players with moderate preferences face lobby groups with extreme preferences, or if there are two opposing coalitions with an equal number of members. Otherwise, there are always free riders among the players.
Keywords: Group formation; Rent-seeking; Free riding

Computation on Encrypted Data Using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kußmaul, Jörn; Janneck, Jonas; Kerschbaum, Florian; Bodden, Eric (ACM Transactions on Privacy and Security)
Encrypting data before sending it to the cloud ensures data confidentiality but requires the cloud to compute on encrypted data. Trusted execution environments, such as Intel SGX enclaves, promise to provide a secure environment in which data can be decrypted and then processed. However, vulnerabilities in the executed program give attackers ample opportunities to execute arbitrary code inside the enclave. This code can modify the dataflow of the program and leak secrets via SGX side channels. Fully homomorphic encryption would be an alternative to compute on encrypted data without data leaks. However, due to its high computational complexity, its applicability to general-purpose computing remains limited. Researchers have made several proposals for transforming programs to perform encrypted computations on less powerful encryption schemes. Yet current approaches do not support programs making control-flow decisions based on encrypted data. We introduce the concept of dataflow authentication (DFAuth) to enable such programs. DFAuth prevents an adversary from arbitrarily deviating from the dataflow of a program. Our technique hence offers protections against the side-channel attacks described previously. We implemented two flavors of DFAuth, a Java bytecode-to-bytecode compiler, and an SGX enclave running a small and program-independent trusted code base. We applied DFAuth to a neural network performing machine learning on sensitive medical data and a smart charging scheduler for electric vehicles. Our transformation yields a neural network with encrypted weights, which can be evaluated on encrypted inputs in \( 12.55 \,ms \) . Our protected scheduler is capable of updating the encrypted charging plan in approximately 1.06 seconds.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric generalized autoregressive conditional heteroscedasticity (GARCH) models with long memory are introduced. A multiplicative decomposition of the volatility into a conditional component and an unconditional component is assumed. The estimation of the latter is carried out by means of a data-driven local polynomial smoother. According to the revised recommendations by the Basel Committee on Banking Supervision to measure market risk in the banks’ trading books, these new semiparametric GARCH models are applied to obtain rolling one-step ahead forecasts for the value-at-risk and expected shortfall (ES) for market risk assets. Standard regulatory traffic-light tests and a newly introduced traffic-light test for the ES are carried out for all models. In addition, model performance is assessed via a recently introduced model selection criterion. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long-memory GARCH models are a meaningful substitute for their conventional, parametric counterparts.
Keywords: long memory; generalized autoregressive conditional heteroscedasticity (GARCH) models; value-at-risk (VaR); expected shortfall (ES); traffic-light test; backtesting

Decision-making under Imperfect Information with Bayesian Learning or Heuristic Rules - Burs, Carina; Gries, Thomas
Information is one of the most important ingredients for decision-making. While the neoclassical assumption of perfect information is surely an important conceptual benchmark for discussing efficient allocations, it is obviously far from describing a rational choice under real conditions. In reality, optimal choices should be considered choices under imperfect information. Thus, decision-makers' information problem can be solved by two strategies. Either they collect an optimal set of information to make an optimal allocation choice under this imperfect information set or they can apply heuristic reasoning. In this paper, we suggest a formal model framework for the example of a simple consumer decision for the allocation of differentiated goods to explore information acquisition strategies in such a simple standard choice situation. Using the model variation under perfect information as a benchmark, we answer the following questions. First and most importantly, under imperfect information, can a heuristic rule substitute information acquisition as an optimal choice? Second, what is the role of risk aversion in the information acquisition process? Finally, we explore the differences to the benchmark, both ex ante the first purchase decision and ex post when repeated purchases and consumption allows for experiences with the choices made.
Keywords: information economics; imperfect information; Bayesian learning; risk; heuristics; differentiated products

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric GARCH models with long memory are in- troduced. The estimation of the nonparametric scale function is carried out by an adapted version of the SEMIFAR algorithm (Beran et al., 2002). Recurring on the revised recommendations by the Basel Committee to measure market risk in the banks' trading books (Basel Committee on Banking Supervision, 2013), the semi- parametric GARCH models are applied to obtain rolling one-step ahead forecasts for the Value at Risk (VaR) and Expected Shortfall (ES) for market risk assets. In addition, standard regulatory traffic light tests (Basel Committee on Banking Supervision, 1996) and a newly introduced traffic light test for the ES are carried out for all models. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long memory GARCH models are an attractive alternative to their conventional, parametric counterparts.
Keywords: Semiparametric; long memory; GARCH models; forecasting; Value at Risk; Expected Shortfall; traffic light test; Basel Committee on Banking Supervision

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa
This study examines the relation between voluntary audit and the cost of debt in private firms. We use a sample of 4,058 small private firms operating in the period 2006‐2017 that are not subject to mandatory audits. Firms decide for a voluntary audit of financial statements either because the economic setting in which they operate effectively forces them to do so (e.g., ownership complexity, export‐oriented supply chain, subsidiary status) or because firm fundamentals and/or financial reporting practices limit their access to financial debt, both reflected in earnings quality. We use these factors to model the decision for voluntary audit. In the outcome analyses, we find robust evidence that voluntary audits are associated with higher, rather than lower, interest rate by up to 3.0 percentage points. This effect is present regardless of the perceived audit quality (Big‐4 vs. non‐Big‐4), but is stronger for non‐Big‐4 audits where auditees have a stronger position relative to auditors. Audited firms’ earnings are less informative about future operating performance relative to unaudited counterparts. We conclude that voluntary audits facilitate access to financial debt for firms with higher risk that may otherwise have no access to this form of financing. The price paid is reflected in higher interest rates charged to firms with voluntary audits – firms with higher information and/or fundamental risk.
Keywords: private firms; voluntary audit; cost of debt; self‐selection bias; risk

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Risk allocation through securitization - Evidence from non-performing loans - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing a unique and hand-collected dataset of securitization transactions by European banks, this paper analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios (NPLRs). We provide evidence for an NPLR-reducing effect during the boom phase of securitizations suggesting that banks (partly) securitized NPLs as the most risky junior tranche. In contrast, we find the reverse effect during the crises period indicating that issuing banks demonstrated `skin in the game'. A variety of sensitivity analyses provides further important implications for the vital debate on reducing NPL exposures and regulating securitization markets.
Keywords: European Banking; Non-performing Loans; Risk Allocation; Securitization

Prudence and prevention: Empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik
Theoretical papers show that optimal prevention decisions in the sense of selfprotection (i.e., primary prevention) depend not only on the level of (second-order) risk aversion but also on higher-order risk preferences such as prudence (third-order risk aversion). We study empirically whether these theoretical results hold and whether prudent individuals show less preventive (self-protection) effort than non-prudent individuals. We use a unique dataset that combines data on higher-order risk preferences and various measures of observed real-world prevention behavior. We find that prudent individuals indeed invest less in self-protection as measured by influenza vaccination. This result is driven by high risk individuals such as individuals >60 years of age or chronically ill. We do not find a clear empirical relationship between riskpreferences and prevention in the sense of self-insurance (i.e. secondary prevention). Neither risk aversion nor prudence is related to cancer screenings such as mammograms, Pap smears or X-rays of the lung.
Keywords: prudence; risk preferences; prevention; vaccination; screening

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; credit risk transfer; effective tax rates; European banking

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS spread changes - Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We find that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric five-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline finding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Are cryptocurrency traders pioneers or just risk-seekers? evidence from brokerage accounts - Pelster, Matthias; Breitmayer, Bastian; Hasso, Tim (Economics Letters)
Are cryptocurrency traders driven by a desire to invest in a new asset class to diversify their portfolio or are they merely seeking to increase their levels of risk? To answer this question, we use individual-level brokerage data and study their behavior in stock trading around the time they engage in their first cryptocurrency trade. We find that when engaging in cryptocurrency trading investors simultaneously increase their risk-seeking behavior in stock trading as they increase their trading intensity and use of leverage. The increase in risk-seeking in stocks is particularly pronounced when volatility in cryptocurrency returns is low, suggesting that their overall behavior is driven by excitement-seeking.
Keywords: cryptocurrencies; bitcoin; investor; risk-seeking

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS-Spread changes - Uhde, André; Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We nd that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric ve-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline nding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

The relationship between credit risk transfer and non-performing loans. Evidence from European banks - Uhde, André; Wengerek, Sascha Tobias
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks' non-performing loan to total assets ratios (NPLRs). We provide evidence for an NPLR-reducing effect during the boom phase of securitizations in Europe suggesting that banks in our sample may (partly) securitize NPLs as the most risky junior tranche and do not (fully) retain NPLs as a reputation and quality signal towards less informed investors in imperfect capital markets. In contrast, we fi nd the reverse effect during the crises period in Europe indicating that issuing banks provided credit enhancement and demonstrated `skin in the game'. Our baseline result remains robust when controlling for endogeneity concerns and a potential persistence in the time series of the NPL data. Moreover, results from a variety of sensitivity analysis reveal that the NPLR-reducing effect is stronger for opaque securitization transactions, for issuing banks exhibiting higher average levels of NPLRs and for banks operating from non-PIIGS countries. In addition, a reduction of NPLRs through securitization is observed for issued collateralized debt obligations, residential mortgage-backed securities, consumer and other unspeci ed loans as well as for non-frequently issuing, systemically less important and worse-rated banks. Our analysis offers essential insights into the loan risk allocation process through securitization and provides important implications for the vital debate on reducing NPL exposures and the process of revitalizing and regulating the European securitization market.
Keywords: European Banking; Non-performing Loans; Risk Allocation; Securitization

Contrasting Risk Perceptions of Technology-Based Service Innovations in Inter-Organizational Settings. - Paluch, Stefanie; Wünderlich, Nancy (Journal of business Research)
Despite the rapid growth and potential of technology-based services, managers' greatest challenges are gaining customer acceptance and increasing usage of these new innovative services. In the B2C field, studies of self-service technology show that perceived risk is an important factor influencing the use of service technology. Though prior research explores different risk types that emerge in consumer settings, risk perception in the B2B setting lacks a detailed examination of different risk types influencing technology-based service adoption. Data from 49 qualitative interviews with providers and customers in two different B2B industries inform this study. The findings emphasize the importance of functional and financial risks in a B2B context and show that business customers' personal and psychological fears hinder their use of technology-based services. Results highlight differences in risk perception and evaluation between customers and providers.
Keywords: Risk perception; Technology-based service innovations; Business-to-business context; Interview study; Risk categories; Smart service

Risk-taking incentives through excess variable compensation: Evidence from European banks - Uhde, André (The Quarterly Review of Economics and Finance)
Employing compensation data provided by 63 banks from 16 European countries for the period from 2000 to 2010 this paper empirically investigates the impact of excess variable compensation on bank risk. As a main finding, we provide evidence for a risk-increasing impact of excess variable pay for both executive variable cash-based and variable equity-based compensation. This baseline finding holds under various robustness checks, in particular when controlling for likely reverse causality between bank risk and variable compensation by employing Granger-causality tests and instrumental variable regressions. In addition, results from a large number of sensitivity analyses including board and banking characteristics as well as the financial crisis period and the quality of a country's regulatory framework provide further important implications for banking regulators and politicians in Europe.
Keywords: Banking; Executive compensation; Risk-taking; Financial stability

Risk Reduction in Natural Disaster Management Through Information Systems: A Literature review and an IS design science research agenda - Schryen, Guido; Wex, Felix (International Journal of Information Systems for Crisis Response and Management (IJISCRAM))
Natural disasters, including earthquakes, Tsunamis, floods, hurricanes, and volcanic eruptions, have caused tremendous harm and continue to threaten millions of humans and various infrastructure capabilities each year. In their efforts to take countermeasures against the threats posed by future natural disasters, the United Nations formulated the ?Hyogo Framework for Action?, which aims at assessing and reducing risk. This framework and a global review of disaster reduction initiatives of the United Nations acknowledge the need for information systems research contributions in addressing major challenges of natural disaster management. In this paper, we provide a review of the literature with regard to how information systems research has addressed risk assessment and reduction in natural disaster management. Based on the review we identify research gaps that are centered around the need for acquiring general knowledge on how to design IS artifacts for risk assessment and reduction. In order to close these gaps in further research, we develop a research agenda that follows the IS design science paradigm.
Keywords: Natural Disaster Management; Risk Reduction; Hyogo Framework; IS Design Science; Literature review

Low temperature fabrication of a ZnO nanoparticle thin-film transistor suitable for flexible electronics - Vidor, F.F.; Wirth, G.I.; Hilleringmann, Ulrich (Microelectronics Reliability)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Safety; Risk; Reliability and Quality; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Determinants of market beta: the impacts of firm-specific accounting figures and market conditions - Schlueter, Tobias; Sievers, Sönke (Review of Quantitative Finance and Accounting (VHB-JOURQUAL 3 Ranking B))
This article examines and extends research on the relation between the capital asset pricing model market beta, accounting risk measures and macroeconomic risk factors. We employ a beta decomposition approach that nests competing models with different business risk proxies and allows to frame cross-model comparison. Because model tests require estimated independent variables resulting in measurement error, we empirically estimate three comparable model specifications with instrumental variable estimators and for the first time provide thorough instrument diagnostics in this setting. Correcting for the heretofore neglected weak instruments problem we find that growth risk (i.e., the risk of firm sales variations that are inconsistent with the market wide trends), is the business risk that explains cross-sectional variations in market beta best.
Keywords: CAPM; Cost of capital; Accounting beta; Intrinsic business risk; Growth risk; Instrumental variables

Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Wealth effects of credit risk securitization in European Banking - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Business Finance and Accounting)
Using a unique cross‐sectional dataset of 381 cash and synthetic securitizations issued by 53 banks from the EU‐15 plus Switzerland between 1997 and 2007, this paper provides empirical evidence for time‐dependent negative wealth effects of credit risk securitization announcements in European banking. Baseline results hold when comparing estimated wealth effects with a control group of similar but non‐securitizing banks for the relevant time period. Moreover, building several sub samples we find that the nexus between credit risk securitization, the issuing banks’ overall risk exposure and wealth effects is associated with a variety of transaction‐ and bank‐specific factors.
Keywords: wealth effects; credit risk securitization; Europe; event study

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

The Nexus between Monetary Policy, Banking Market Structure and Bank Risk Taking - Michalak, Tobias C.; Uhde, André
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.
Keywords: risk-taking channel; competition; concentration; bank soundness; European banking

Securitization and systematic risk in European banking: Empirical evidence - Uhde, André; Michalak, Tobias C. (Journal of Banking & Finance)
Using a unique dataset of 592 cash and synthetic securitizations issued by 54 banks from the EU-15 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a positive impact on the increase of European banks’ systematic risk. Baseline results hold when comparing estimated beta coefficients with a control group of similar non-securitizing banks. Building several sub-samples we additionally find that (a) the increase in systematic risk is more relevant for larger banks that repeatedly engage in securitization, (b) securitization is more important for small and medium financial institutions, (c) banks have a higher incentive to retain the larger part of credit risk as a quality signal at the beginning of the securitization business in Europe, and (d) the overall risk-shifting effect due to securitization is more distinct when the pre-event systematic risk is low.
Keywords: Credit risk transfer; Securitization; Systematic risk; Event study